The Influence of Work Stress, Workload and Job Satisfaction On Employee Performance at PT. Karoseri Laksana: The Influence of Work Stress, Workload and Job Satisfaction On Employee Performance at PT. Karoseri Laksana - Sefila amelia, Sefila; Sijabat, Rauly; Ervina Indiworo, Rr Hawik (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the influence of workload, work stress, and job satisfaction on employee performance at PT. Karoseri Laksana Ungaran, Semarang Regency. The data in this research uses primary data obtained from questionnaires using the Nonprobability Sampling technique (Saturated Sample). The population is 245 respondents from body parts such as production departments. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have also been tested in the form of normality assumptions, heteroscedasticity assumptions, multicollinearity assumptions and autocorrelation. The data analysis method uses multiple regression techniques. The research results show that work stress has a positive effect on employee performance, workload has a negative effect on employee performance and job satisfaction has a positive effect on employee performance.